2018
DOI: 10.1111/jpn.13016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of recombinant Cry and Cp4 epsps proteins on haematological indices of growing rabbits

Abstract: Genetically modified (GM) crops expressing insect resistance and herbicide tolerance provide a novel approach for improved crop production but their advent at the same time presents serious challenges in terms of food safety. Although prevailing scientific proof has suggested that transgenic crops are analogous to their conventional counterparts, their use in human and animal diet gave rise to emotional public discussion. A number of studies had been conducted to evaluate the potential unintended effects of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…Our biosafety study on wister rats, which involved using 40% GM cottonseed as a diet in (G3) group and 30% Non-GM cottonseed as diet in (G2) group, showed no comparable change of harmful effect on LFT, RFT and serum electrolyte when compared to the standard diet control group (G1). These results are consistent with the previous studies 20 , 36 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our biosafety study on wister rats, which involved using 40% GM cottonseed as a diet in (G3) group and 30% Non-GM cottonseed as diet in (G2) group, showed no comparable change of harmful effect on LFT, RFT and serum electrolyte when compared to the standard diet control group (G1). These results are consistent with the previous studies 20 , 36 .…”
Section: Discussionsupporting
confidence: 94%
“…Rats in group G1 were reared on standard diet while rats in G2 and G3 were respectively reared on a diet containing non-transgenic and 40% of transgenic cotton seeds (expressing Cy1Ac, Cry2A and cp4EPSPS) or it’s near isogenic one. Animals were kept for 90 days under standard housing conditions 20 . At the end of the study blood samples were collected from all the animal groups in a serum separator tubes and sent to university of veterinary and animal science (diagnostic lab) for liver function test (LFT), renal function test (RFT) and serum electrolyte.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 50 Wistar rats (25 males and 25 females, aged 5–6 weeks old at the start of the experiment) were kept at the CEMB animal house. The animal’s distribution and their housing were as described by Salisu et al [ 37 , 38 ] in earlier studies. The procedures of housing and treatments were approved by the ethics committee of the CEMB.…”
Section: Methodsmentioning
confidence: 99%
“…After the 90 days feeding trial, ovaries and testes were removed and cut into 2.0 cm segments, placed in RNAlater (Invitrogen) and stored at 4°C overnight. RNA was isolated using the Trizol method (Invitrogen) as described earlier by Salisu et al, [ 37 ]. The extracted RNA was resuspended in RNase-Free water and then quality and integrity were evaluated using the NanoDrop 1000 spectrophotometer (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the effects of transgenic plants on domestic animals and the environment have been intensively studied [ 9 ]. CP4-EPSPS shows no obvious similarity with proteins associated with allergy and toxicity [ 10 ], and several investigations indicated that doses of CP4-EPSPS much higher than the dietary supplement level had no obvious toxicological effect on the reproductive function in rats [ 11 , 12 ] or animal health as a dietary supplementation [ 13 ]. However, some research has still raised possibilities that these plants may cause unintended effects via different pathways, which have to be systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%